Convenient one-pot synthesis of 1, 2, 4-oxadiazoles and 2, 4, 6-triarylpyridines using graphene oxide (GO) as a metal-free catalyst: importance of dual catalytic activity. Issue 51 (28th September 2021) - Basak, Puja; Dey, Sourav; Ghosh, Pranab
Abstract : Graphene oxide (GO) as a metal-free catalyst for the synthesis of 1, 2, 4-oxadiazoles and 2, 4, 6-triarylpyridines under mild reaction conditions. Abstract : A convenient and efficient process for the synthesis of 3, 5-disubstituted 1, 2, 4-oxadiazoles and 2, 4, 6-triarylpyridines has been described using an inexpensive, environmentally benign, metal-free heterogeneous carbocatalyst, graphene oxide (GO). GO plays a dual role of an oxidizing agent and solid acid catalyst for synthesizing 1, 2, 4-oxadiazoles and triarylpyridines. This dual catalytic activity of GO is due to the presence of oxygenated functional groups which are distributed on the nanosheets of graphene oxide. A broad scope of substrate applicability and good sustainability is offered in this developed protocol. The results of a few control experiments reveal a plausible mechanism and the role of GO as a catalyst was confirmed by FTIR, XRD, SEM, and HR-TEM analysis.